Analysis and classification of control and access control systems at the enterprise - Юдін, О.К.; Весельська, О.М. (Science-based technologies, 2018)
The analysis of existing systems of control of access control is conducted, types and levels of network interaction between its blocks are given. Classification of automated access control systems according to different criteria is given. The four classes of ACS are given depending on the degree of delimitation and access security required by the company. The recommendations for using different types of interfaces are given. It has been discovered that control and access control systems can be effectively used not only as access control for the enterprise, but also as a means for the accumulation of information important for decision-making.